Effects of high-intensity interval training on strength, speed, and endurance performance among racket sports players: A systematic review - Liu, Y.; Abdullah, B. B.; Abu Saad, H. B. (PLOS ONE, 2024)
This study aims to present a critical review of the existing literature on the effects of High-Intensity Interval Training (HIIT) on strength, speed, and endurance performance among racket sports athletes. This study conducted a systematic literature review by PRISMA guidelines. Various well-known academic and scientific databases were used for research collection, including PubMed, EBSCOhost, Scopus, Web of Science, and Google Scholar. Out of 27 relevant studies, 10 were selected for inclusion in this systematic review, all meeting the required inclusion criteria. The quality of each study was assessed using the PEDro scale, with scores ranging from 3 to 5 for the selected studies. HIIT was found to improve racket players` VO2 max (maximum oxygen uptake), running and repetitive sprint performance, jumping performance, and hitting speed during play. Current findings indicate that HIIT can significantly benefit athletic performance. Long-term HIIT allows athletes to enhance their power while improving crucial variables related to both aerobic and anaerobic endurance. This anaerobic endurance and explosive power type is particularly vital for racket sports players. For example, athletes in table tennis and badminton must exert maximum effort during high-intensity middle and back-court play. Racket athletes also need to maintain a stable state while preserving ball speed and positioning, and must quickly recover to prepare for the next rally. This training mechanism can assist athletes in honing their skills and achieving more efficient hitting quality. Therefore, this paper recommends that racket sports athletes incorporate HIIT into their regular training routines. The suggested frequency is three times per week, with each training session lasting 30-40 minutes, and a total duration of six to eight weeks.